Atomic-scale dispersed iron-based nitrogen-oxygen doped carbon material and preparation method and application thereof
By designing atomically dispersed iron-based nitrogen-oxygen doped carbon materials, and regulating the coordination structure between iron atoms and nitrogen-oxygen, the problem of low catalytic activity of existing catalysts activated PMS is solved, efficient activation of PMS and efficient degradation of various pollutants is achieved, and the wastewater treatment effect is significantly improved.
Patent Information
- Application Number
- CN202411758939.4
- Authority / Receiving Office
- CN · China
- Patent Type
- Applications(China)
- Current Assignee / Owner
- Priority Date
- 2024-05-21
- Filing Date
- 2024-12-03
- Publication Date
- 2025-03-28
AI Technical Summary
The catalytic activity of existing catalysts is not high when activating persulfate (PMS), and it is difficult to affect the activity of single-atom catalysts through coordination regulation of metal ion centers.
A kind of atomically dispersed iron-based nitrogen-oxygen doped carbon material is designed to improve catalytic activity by regulating the coordination structure between iron atoms and nitrogen-oxygen. This material carries iron-nitrogen-oxygen structures at high temperatures through the combination of dimethylimidazole, iron phthalocyanine and zinc nitrate hexahydrate, achieving efficient activation of PMS.
The catalytic performance of PMS is significantly improved, allowing it to efficiently degrade a variety of pollutants through multiple pathways (free radicals and non-free radicals), significantly improve the wastewater treatment effect, and have good catalytic stability.
Smart Images

Figure CN119702038A_ABST
Abstract
Description
Technical Field
[0001] This invention relates to the field of wastewater treatment technology, and in particular to an atomically dispersed iron-based nitrogen-oxygen-doped carbon material, its preparation method, and its application. Background Technology
[0002] In water pollution treatment, persulfate (PMS) activation technology is considered an effective advanced oxidation technology for degrading recalcitrant water pollutants due to its high reactivity and mild reaction conditions.
[0003] PMS can be activated by methods such as ultraviolet irradiation, ultrasound, and electrochemical processes. Activated PMS can generate reactive species such as sulfate radicals, hydroxyl radicals, and superoxide radicals through free radical processes, and can also generate singlet oxygen, high-valence metals, and surface electron transfer through non-free radical processes. The redox potentials of the three common reactive oxygen species (ROS) are SO4·- (2.5-3.1V vs NHE), ·OH (1.9-2.7V vs NHE), and... 1 O2 (0.81V vs NHE). Hydroxyl radicals and sulfate radicals possess strong oxidizing power, but they require very specific reaction conditions, making them difficult to apply in practical wastewater treatment. Non-radical processes such as singlet oxygen and surface electron transfer are considered effective methods for degrading recalcitrant organic pollutants due to their excellent selectivity and resistance to interference. Therefore, developing specific catalysts to selectively induce PMS activation is of great significance for improving its wastewater treatment efficiency.
[0004] In recent years, carbon materials, especially transition metals and carbon-nitrogen co-doped (MNC) materials, have been widely used as heterogeneous catalysts for advanced oxidation processes. With the development of smaller catalyst sizes, from micrometers to single-atom catalysts (SAC), atom utilization and catalytic efficiency can be significantly improved. However, current catalysts exhibit low activity in persulfate reactions, and the mechanism by which the coordination of metal ion centers can alter the surrounding electron density and thus affect the activity of single-atom catalysts remains unclear.
[0005] Therefore, in order to improve the catalytic performance of advanced oxidation systems based on persulfate, it is of great significance to explore whether the coordination environment of SAC can be adjusted to control the catalytic activity, design a novel co-doped single-atom-level catalyst and improve its catalytic activity, which can enhance the treatment effect of PMS. Summary of the Invention
[0006] The purpose of this invention is to overcome the shortcomings of existing technologies and provide an atomically dispersed iron-based nitrogen-oxygen-doped carbon material, its preparation method, and its applications. The material provided by this invention can serve as a catalyst for activating persulfate, significantly improving its efficiency in degrading water pollutants, and has extremely high application value.
[0007] To achieve the above objectives, the technical solution adopted by the present invention is as follows:
[0008] In a first aspect, the present invention provides a method for preparing an atomically dispersed, iron-based, site-anchored nitrogen-oxygen-doped carbon material, characterized by comprising the following steps:
[0009] (1) Mix solution A and solution B, then centrifuge, wash and evaporate to dryness to obtain the precursor; the components of solution A include dimethylimidazole and iron phthalocyanine; the components of solution B include zinc nitrate hexahydrate.
[0010] In solution A, the concentration of dimethylimidazole is 0.06-0.08 g / mL; in solution B, the concentration of zinc nitrate hexahydrate is 0.02-0.04 g / mL; the volume ratio of solution A to solution B is 1:(0.9-1.1).
[0011] (2) The precursor is carbonized, cooled, cleaned and dried to obtain the atomically dispersed iron-based nitrogen-oxygen doped carbon material.
[0012] The preparation method of this invention first prepares a precursor: dimethylimidazole and iron phthalocyanine are initially used to form a relatively stable ligand structure in solution, and then zinc nitrate hexahydrate is prepared into a solution and fully dissolved. The above solution is then mixed and centrifuged to obtain the precursor. Dimethylimidazole provides the carbon and nitrogen sources, and zinc nitrate hexahydrate provides the oxygen element. Subsequently, the precursor is further carbonized: the vacancies left by zinc volatilization are occupied by iron, allowing oxygen to form a stable bond with iron, resulting in a single-atom dispersed iron-nitrogen-oxygen structure, achieving coordination regulation; while some zinc sites not occupied by iron form unique functionalized free active sites.
[0013] The above preparation method yields carbon materials with atomically dispersed iron-nitrogen-oxygen (FeN2O2) coordination doped structures, which enhances their performance as catalysts for activating persulfates. This material effectively activates persulfates, causing them to react with both free radicals (SO4·- and ·OH) and non-free radicals (SO4·- and ·OH). 1 Multiple pathways (including O2 and direct electron transfer) are used to achieve efficient degradation of various pollutants and significantly improve wastewater treatment.
[0014] Under specific concentrations and ratios of dimethylimidazole and zinc nitrate hexahydrate, zinc nitrate hexahydrate provides sufficient adsorption sites for iron atoms to occupy, ensuring the formation of atomically dispersed iron-based sites and preventing the aggregation of iron atoms that could affect catalyst performance. Dimethylimidazole provides suitable N coordination sites, thus comprehensively achieving atomic dispersion and coordination regulation. If the concentrations of dimethylimidazole and zinc nitrate hexahydrate are outside the aforementioned range, the atomic dispersion of iron sites and their coordination with N and O will be affected, leading to changes in the material structure. This will impact the catalyst's advanced oxidation activation performance for persulfate, thereby reducing the efficiency of water pollutant treatment.
[0015] The preparation method of this invention can regulate parameters such as the nitrogen and oxygen doping degree and specific surface area of the material by adjusting the raw material ratio of the precursor, changing the carbonization temperature, heating rate, and carbonization time, thereby altering the catalytic active sites and affecting the catalytic activity. Simultaneously, the raw materials used in the preparation of the material are inexpensive, the synthesis method is simple, and it can serve as a good catalyst, exhibiting excellent catalytic stability and activity in the treatment of advanced oxidation water pollution, which is beneficial for the engineering application of the material.
[0016] Preferably, in step (1), the mass ratio of ferrophthalocyanine to dimethylimidazole in solution A is (0.5-1.5):100. At this ratio of dimethylimidazole, ferrophthalocyanine, and zinc nitrate hexahydrate, the spacing between adjacent iron atoms in the prepared material can be better controlled. The atomically dispersed iron site anchoring structure formed during the high-temperature reaction enhances the advanced oxidation activation performance of persulfate.
[0017] Preferably, in step (1), the solvent for both solution A and solution B is anhydrous methanol; the evaporation temperature is 70-80℃. Using methanol as a solvent, and ensuring thorough mixing of the components during the preparation of solutions A and B (stirring time approximately 3 hours), effectively disperses the organic substrate and metal salt during the reaction, facilitating the preparation of atomically dispersed single-atom iron catalysts.
[0018] More preferably, in step (1), the cleaning process involves washing with anhydrous methanol, evaporating the solution, and then adding anhydrous methanol for the next cleaning cycle, for a total of three cleaning cycles. This cleaning process helps improve the purity of the precursor and promotes the formation of a stable structure.
[0019] Preferably, in step (2), the carbonization temperature is 800-1000℃.
[0020] More preferably, in step (2), the carbonization temperature is 900°C.
[0021] When the carbonization temperature is controlled at 800-1000℃, the prepared material can improve the catalytic activation effect and significantly enhance the degradation effect of activated persulfate on pollutants in wastewater. When the high-temperature carbonization temperature is controlled at 900℃, the material has the best effect, which can catalyze the activation of persulfate, significantly shorten the time required for pollutant degradation, and improve wastewater treatment efficiency.
[0022] More preferably, in step (2), the carbonization conditions are: in an inert atmosphere, the temperature is increased to 800-1000℃ at a rate of 3-8℃ / min, and then kept at that temperature for 2-5 hours.
[0023] The inert atmosphere provides a stable environment for high-temperature carbonization on a safe basis. The above-mentioned high-temperature carbonization process realizes the formation of iron-nitrogen-oxygen coordination structure and completes the anchoring of iron atoms on nitrogen-oxygen doped carbon.
[0024] Preferably, in step (2), the cleaning includes pickling and water washing; the concentration of the pickling solution used for pickling is 0.25-0.75M, and the pickling time is 12-72h.
[0025] Preferably, 0.5M sulfuric acid is used in the pickling process, which can remove impurities, oxides or other undesirable substances from the material surface, further improving the activity and stability of the catalyst.
[0026] More preferably, in step (2), the washing time is 20-25 hours and the drying temperature is 60-80°C.
[0027] Secondly, the present invention provides an atomically dispersed iron-based nitrogen-oxygen-doped carbon material prepared by the above-described preparation method.
[0028] Preferably, the iron content in the material is 0.2-0.5% by mass percentage.
[0029] The atomically dispersed iron-based nitrogen-oxygen-doped carbon material can selectively adsorb a variety of recalcitrant new pollutants and efficiently activate persulfate to rapidly degrade these pollutants. Furthermore, the degradation process works synergistically through multiple pathways, which not only greatly improves degradation efficiency but also has strong anti-interference capabilities and high atom utilization, making it applicable to industrial wastewater or sewage treatment.
[0030] Thirdly, the present invention provides an application of the above-mentioned atomically dispersed iron-based nitrogen-oxygen-doped carbon material in wastewater treatment.
[0031] Preferably, the wastewater treatment includes the following steps:
[0032] The atomically dispersed iron-based nitrogen-oxygen-doped carbon material and persulfate are added to the wastewater to be treated.
[0033] Preferably, the concentration of atomically dispersed iron-based nitrogen-oxygen-doped carbon material in the treated wastewater is 20-100 mg / L, and the concentration of persulfate is 0.5-2.0 mmol / L.
[0034] More preferably, the processing time is 10-30 minutes.
[0035] To achieve optimal treatment results in wastewater treatment, the type and concentration of pollutants in the wastewater must be considered. The dosage of the aforementioned materials and persulfate should be determined based on the specific composition of the wastewater. Generally, the recommended concentrations are 20-100 mg / L for the materials and 0.5-2.0 mmol / L for the persulfate. Adjusting the concentration can treat wastewater with high pollutant content; specific ratios can be optimized through experiments for different types of wastewater. This application ensures the effective coordination of catalysts and oxidants during wastewater treatment, thereby improving treatment efficiency and effectiveness.
[0036] Compared with the prior art, the beneficial effects of the present invention are as follows:
[0037] The preparation method provided by this invention introduces zinc nitrate hexahydrate with high oxygen content, providing oxygen for bonding with iron atoms to synthesize an iron-nitrogen-oxygen structure, achieving atomic-level coordination control of the material. By coordinating the active centers of iron metal atoms, the prepared atomically dispersed iron-based nitrogen-oxygen-doped carbon material can be used as a catalyst to selectively adsorb various recalcitrant new pollutants and efficiently activate persulfate to degrade recalcitrant new pollutants through multiple pathways of free radicals and non-free radicals, broadening the application range of advanced oxidation water pollution treatment and exhibiting excellent catalytic stability. Its atomically dispersed metal site structure has high atomic utilization, which can significantly improve the degradation rate of pollutants in advanced oxidation water pollution treatment. Attached Figure Description
[0038] Figure 1 The image shows a scanning electron microscope (SEM) image of the atomically dispersed iron-based nitrogen-oxygen-doped carbon material prepared in Example 1.
[0039] Figure 2 This is a transmission electron microscope (TEM) image of the atomically dispersed iron-based nitrogen-oxygen-doped carbon material prepared in Example 1.
[0040] Figure 3 The image shows an aberration-corrected transmission electron microscope (HADDF-TEM) image of the atomically dispersed iron-based nitrogen-oxygen-doped carbon material prepared in Example 1.
[0041] Figure 4 Synchrotron radiation data of the atomically dispersed iron-based nitrogen-oxygen-doped carbon material prepared in Example 1 and the standard sample;
[0042] Figure 5The graph shows the degradation effect of PMS activated with the materials prepared in Examples 1 and Comparative Example 1 on bisphenol A.
[0043] Figure 6 The graph shows the degradation effect of PMS activated by the material prepared in Comparative Example 2 on bisphenol A.
[0044] Figure 7 The graph shows the degradation effect of PMS activated by the materials prepared in comparative examples 3, 4, and 6 on bisphenol A.
[0045] Figure 8 EPR spectrum (SO4·- and ·OH) of the FeN2O2+PMS degradation system for bisphenol A;
[0046] Figure 9 EPR spectrum of the FeN2O2+PMS degradation system for bisphenol A ( 1 O2);
[0047] Figure 10 EPR spectrum (DMPOX) of the FeN2O2+PMS degradation system for bisphenol A;
[0048] Figure 11 Chronoamperometry of the FeN2O2+PMS degradation system for bisphenol A. Detailed Implementation
[0049] To better illustrate the purpose, technical solution, and advantages of the present invention, the present invention will be further described below in conjunction with specific embodiments. Unless otherwise specified, the experimental methods used in the following embodiments are conventional methods; the materials and reagents used, unless otherwise specified, are commercially available reagents and materials.
[0050] Example 1
[0051] An embodiment of the atomically dispersed iron-based nitrogen-oxygen-doped carbon material provided by this invention, wherein the preparation method of the material in this embodiment is as follows:
[0052] (1) Add 2.672 g of dimethylimidazole and 24 mg of phthalocyanine iron to 40 ml of anhydrous methanol, mix well and stir for 3 hours to obtain solution A; wherein the concentration of dimethylimidazole is 0.067 g / mL and the mass ratio of phthalocyanine iron to dimethylimidazole is 0.9:100;
[0053] Add 1.19 g of zinc nitrate hexahydrate to another 40 ml of anhydrous methanol, mix well and stir for 3 hours to obtain solution B; the concentration of zinc nitrate hexahydrate is 0.030 g / mL.
[0054] Solution A and solution B were mixed and stirred at room temperature for 24 hours to obtain a mixed solution (the mass ratio of dimethylimidazole to zinc nitrate hexahydrate was 2.245:1). The solution was then centrifuged at 10,000 rpm for 5 minutes, washed three times with methanol, centrifuged after each wash, and the supernatant was removed before the next wash. Finally, the solution was vacuum dried overnight at 70°C to obtain the precursor.
[0055] (2) The prepared precursor was subjected to a nitrogen atmosphere at a flow rate of 20 ml / min -1 The airflow velocity and the heating rate are 5℃ / min. -1 The temperature is raised to 900℃ and calcined in a tube furnace for 3 hours for high-temperature carbonization.
[0056] Subsequently, it was acid-washed with 0.5M H2SO4 for 24 hours, washed with water until neutral, filtered, and dried in vacuum overnight to obtain a black powder, which is the atomically dispersed iron-based nitrogen-oxygen-doped carbon material, hereinafter referred to as FeN2O2 material (FeN2O2-900 / FeN2O2).
[0057] The structure of the FeN2O2 obtained above was characterized and observed: Figure 1 This is a scanning electron microscope (SEM) image of the FeN2O2 material prepared in this embodiment. Figure 2 This is a transmission electron microscope (TEM) image of the FeN2O2 material prepared in this embodiment. Figure 3 The image shows aberration-corrected transmission electron microscope (HADDF-TEM) image of the FeN2O2 material prepared in this embodiment. Figure 4 This is a comparison chart of synchrotron radiation data between the FeN2O2 material prepared in this embodiment and the standard sample.
[0058] Depend on Figure 1-2 Scanning electron microscopy (SEM) and transmission electron microscopy (TEM) images show that the FeN2O2 material obtained by high-temperature calcination at 900℃ in this embodiment still retains the complete dodecahedral shape of ZIF-8. Furthermore, the elements are uniformly distributed on the material surface, and no obvious Fe atom aggregation was found on the surface.
[0059] Depend on Figure 3 Individual Fe atoms anchored throughout the entire structure can be clearly observed using high-angle annular dark-field scanning transmission electron microscopy (HAADF-STEM) (circled areas in the figure). In summary, the material in this embodiment possesses an atomically dispersed iron-based site structure, which is beneficial for its catalytic performance as a single-atom catalyst.
[0060] Depend on Figure 4 Figure (a) shows the near-edge absorption spectrum, which shows that the atomically dispersed metal valence states in the FeN2O2 material prepared in this embodiment are between the valence states of 2 and 3. Figure 4Images (b) and (c) show the Fourier transform extended edge absorption spectrum and fitting analysis diagram of the FeN2O2 material prepared in this embodiment, respectively. It can be seen that FeN2O2 exhibits... A single prominent peak is observed at this location, located in the Fe-O scattering path of Fe2O3. Fe-N scattering path of FePc The results showed that the prepared FeN2O2 material contained obvious Fe-N and Fe-O bonds, achieving coordination regulation of iron, nitrogen, and oxygen.
[0061] Example 2
[0062] This invention provides an embodiment of an atomically dispersed iron-based nitrogen-oxygen-doped carbon material. The difference between the preparation method of this embodiment and that of Embodiment 1 is that, in step (2), the calcination temperature for high-temperature carbonization is 800°C. An atomically dispersed iron-based nitrogen-oxygen-doped carbon material, FeN2O2-800, is thus prepared.
[0063] Example 3
[0064] This invention provides an embodiment of an atomically dispersed iron-based nitrogen-oxygen-doped carbon material. The difference between the preparation method of this embodiment and that of Embodiment 1 is that, in step (2), the calcination temperature for high-temperature carbonization is 1000°C. An atomically dispersed iron-based nitrogen-oxygen-doped carbon material, FeN2O2-1000, is thus prepared.
[0065] Comparative Example 1
[0066] Nitrogen-carbon materials were prepared using the following method:
[0067] (1) 2.672 g of dimethylimidazole was added to 40 ml of anhydrous methanol, mixed thoroughly, and stirred for 3 hours to obtain solution A; 1.19 g of zinc nitrate hexahydrate was added to another 40 ml of anhydrous methanol, mixed thoroughly, and stirred for 3 hours to obtain solution B; solutions A and B were mixed and stirred at room temperature for 24 hours. Then, the mixture was centrifuged at 10,000 rpm for 5 minutes, washed three times with methanol, centrifuged after each wash, and the supernatant was removed before the next wash. Then, the mixture was vacuum dried overnight at 70°C to obtain the precursor.
[0068] (2) The prepared precursor was subjected to a nitrogen atmosphere at a flow rate of 20 ml / min -1 The airflow velocity and the heating rate are 5℃ / min. -1 The temperature is raised to 900℃ and calcined in a tube furnace for 3 hours for high-temperature carbonization. A black powder is obtained, which is the nitrogen-carbon material, hereinafter referred to as CN.
[0069] Comparative Example 2
[0070] The only difference between Comparative Example 2 and Example 1 is that, in step (1), solution B was obtained by adding 0.54g of zinc chloride to another 40ml of anhydrous methanol, mixing thoroughly, and stirring for 3 hours; the Zn mass content in solution B was the same as in Example 1. A single-atom iron-nitrogen material, hereinafter referred to as FeN4, was prepared.
[0071] Comparative Example 3
[0072] The only difference between Comparative Example 3 and Example 1 is that the amount of dimethylimidazole added in step (1) was adjusted to 1.2 g, so that the concentration of dimethylimidazole in solution A was 0.03 g / mL. The prepared material is referred to as FeN2O2-1.2.
[0073] Comparative Example 4
[0074] The only difference between Comparative Example 4 and Example 1 is that the amount of dimethylimidazole added in step (1) was adjusted to 6g, so that the concentration of dimethylimidazole in solution A was 0.15g / mL. The prepared material is referred to as FeN2O2-6.
[0075] Comparative Example 5
[0076] The only difference between Comparative Example 5 and Example 1 is that the amount of zinc nitrate hexahydrate added in step (1) was adjusted to 0.2 g, so that the concentration of zinc nitrate hexahydrate in solution B was 0.005 g / mL. Within this concentration range, a precursor with a ZIF-8 basic framework structure cannot be formed, and the material cannot be prepared.
[0077] Comparative Example 6
[0078] The only difference between Comparative Example 6 and Example 1 is that the amount of zinc nitrate hexahydrate added in step (1) was adjusted to 4g, so that the concentration of zinc nitrate hexahydrate in solution B was 0.1g / mL. The prepared material is simply referred to as FeN2O2-4.
[0079] Example 1
[0080] To investigate the application effect of the atomically dispersed iron-based nitrogen-oxygen-doped carbon material provided by this invention in the treatment of advanced oxidation water pollution, BPA was selected as a model pollutant. The BPA degradation performance of the materials prepared in Examples 1-4 and 6 was tested using activated PMS. The steps are as follows:
[0081] (1) Catalytic degradation experiment was carried out in 50ml centrifuge tubes: the prepared material was ultrasonically treated for 30 minutes and dispersed in water, and then 50ml of BPA (concentration of 60μM) was added to make the concentration of the material in the solution 0.025g / L. Pre-adsorption was carried out for 30 minutes to ensure that the adsorption / desorption equilibrium was reached.
[0082] (2) After reaching adsorption / desorption equilibrium, PMS stock solution was added to initiate the degradation reaction, making the PMS concentration 0.5 mmol / L. 0.5 ml samples were taken at regular intervals, and 0.1 ml methanol and 0.1 ml 0.5 mol / L Na2S2O3 were added immediately to quench the samples. The samples were then filtered through a 0.22 μm aqueous filter to remove material impurities, and the BPA concentration was determined by high performance liquid chromatography (HPLC, Agilent 1260, USA).
[0083] When the atomically dispersed iron-based nitrogen-oxygen-doped carbon material prepared in the examples is added, BPA can be rapidly adsorbed onto the material surface within 1 minute and reach adsorption / desorption equilibrium within 5 minutes. Among them, the FeN2O2-900 prepared in Example 1 has an equilibrium adsorption capacity as high as 273 mg / g, which has a good adsorption effect on pollutants.
[0084] Figure 5 The degradation and adsorption effects of BPA on materials FeN2O2-900, FeN2O2-800, FeN2O2-1000 and CN-activated PMS in Examples and Comparative Example 1 are shown in the figure. Figure 6 The graph shows the degradation and adsorption effect of FeN4-activated PMS on BPA in Comparative Example 2. Figure 7 The graph shows the degradation and adsorption effects of activated PMS on BPA by the materials prepared in Comparative Examples 3, 4, and 6.
[0085] Depend on Figure 5-7 It can be known that:
[0086] After the addition of PMS, the atomically dispersed iron-based nitrogen-oxygen-doped carbon material prepared in the examples showed a significantly better promoting effect on PMS degradation than the comparative example. Furthermore, compared to the materials prepared by FeN2O2-800, FeN2O2-1000, and the comparative example, FeN2O2-900 catalyzed the degradation of BPA, and after adsorption / desorption equilibrium, the residual BPA was essentially completely degraded within 10 minutes, demonstrating a significant improvement in degradation efficiency.
[0087] The CN or FeN4 material structures formed in Comparative Examples 1 and 2 showed significantly worse activation effects on PMS than the FeN2O2 material provided in Example 1 of this invention, with a degradation rate of only about 30% for BPA within 10 minutes. In Comparative Examples 3, 4, and 6, changing the concentrations of dimethylimidazole and zinc nitrate hexahydrate in the solution, placing them outside the scope of this invention, affected the dispersion of iron or the formation of coordination with N and O. The catalytic activation performance of the prepared materials for persulfate was affected. Compared with the material prepared in Example 1 (FeN2O in the figure), their treatment efficiency for BPA pollutants in wastewater was also significantly reduced. Under the same conditions, complete degradation could not be achieved after 10 minutes of treatment.
[0088] Example 2
[0089] To investigate the mechanism of the atomically dispersed iron-based nitrogen-oxygen-doped carbon material provided in this invention in the reaction system of activated PMS for BPA degradation, the following experiments were conducted:
[0090] (1) EPR test:
[0091] Two mg of the FeN2O2 material prepared in Example 1 was used as a catalyst and placed in a 50 mL centrifuge tube. 50 mL of deionized water and 100 mg of PMS were added, and the liquid was thoroughly mixed to ensure uniform dispersion. After the mixture was allowed to stand for 5 minutes, a small portion of the liquid sample was taken out and filtered through a 0.22 μm membrane filter. The filtrate was then mixed uniformly with 10 μL of a solution containing 100 mM of trapping agent (DMPO + TEMP) and injected into a capillary tube. The capillary tube containing the injected sample was then inserted into the resonance cavity of an electron paramagnetic resonance (EPR) device for detection.
[0092] (2) Dual-cavity timing current test:
[0093] To perform chronoamperometry using an electrochemical workstation, a standard three-electrode electrochemical cell was first assembled. This cell pack used Ag / AgCl as the reference electrode, platinum wire as the counter electrode and working electrode, and 0.1M Na2SO4 as the electrolyte.
[0094] A dual-chamber electrolytic cell device was constructed using FeN2O2-coated carbon paper (CP) as the working electrodes for the two electrolytic cells. During the reaction, one cell was filled with BPA solution and the other with PMS solution, separated by a cation exchange membrane, thus constructing the dual-chamber electrolytic cell device.
[0095] Preparation of the working electrode for the above electrolytic cell device: Weigh 5 mg of FeN2O2 material using an electronic balance and place it in a 4 ml sample vial. Simultaneously, add 950 μl of ethanol and 50 μl of 0.5% wt Nafion solution to the sample vial. Sonicate the mixture for 2 hours before use. Cut a 1×3 cm electrode. 2 A piece of hydrophobic carbon paper of a certain size, glued with non-conductive adhesive, leaving a 1×1cm margin. 2 Area. Take 100 μl of the above mixture and gradually add it dropwise onto a 1×1 cm area of hydrophobic carbon paper. 2 In terms of area, the electrodes were prepared by baking them under an infrared lamp for 1 minute and then set aside.
[0096] Figure 8 The EPR spectrum (SO4·- and ·OH) of the PMS degradation system activated by FeN2O2 material in Example 1 is shown. Figure 9 The EPR spectrum of the FeN2O2 material-activated PMS degradation bisphenol A system in Example 1 is shown below. 1 O2); Figure 10 The EPR spectrum (DMPOX) of the PMS degradation system of FeN2O2 material activated in Example 1 is shown. Figure 11 This is a chronoamperometry diagram of the PMS degradation system of FeN2O2 material in Example 1.
[0097] Depend on Figure 8 and Figure 10 It was found that no detectable radical signal was observed when PMS was added alone, using DMPO as the spin-trapping reagent. This finding effectively rules out the possibility that PMS plays a role in BPA degradation through self-dissolution. Conversely, the FeN2O2 / PMS system showed DMPO-OH and DMPO-SO4. - Two EPR signals: This indicates that FeN2O2 material can trigger PMS to generate SO4. ·- and · OH. No superoxide radicals (O2) were observed in the solution after the addition of methanol solution. 2·- Conversely, a signal of 5,5-dimethyl-2-pyrrolidone-N-oxide (DMPOX) was detected, indicating that DMPO had been oxidized by other strong oxidants.
[0098] Depend on Figure 9 It can be seen that when TEMP is used as a spin trapping reagent, no obvious signal is detected in the PMS+TEMP system, but a clear TEMP signal is detected in the FeN2O2+PMS+TEMP system. 1 The O2 1:1:1 triple signal indicates that FeN2O2 can effectively activate PMS to produce... 1 O2.
[0099] Figure 11 The results show that when the BPA solution and PMS solution are separated, the current when FeN2O2-coated carbon paper (CP) is used as the working electrode of the two electrolytic cells is much higher than when carbon paper (CP) is used as the working electrode of the two electrolytic cells alone. This proves that there is an electron transfer mechanism in the reaction process, and electrons are transferred from BPA to PMS through FeN2O2, resulting in the oxidation of BPA.
[0100] In summary, the FeN2O2 material prepared by this invention can effectively activate PMS to produce SO4 through multiple pathways. ·- / · OH or 1 O2 significantly improves the efficiency of PMS in promoting the degradation of pollutants such as BPA.
[0101] Finally, it should be noted that the above embodiments are only used to illustrate the technical solutions of the present invention and are not intended to limit the scope of protection of the present invention. Although the present invention has been described in detail with reference to preferred embodiments, those skilled in the art should understand that modifications or equivalent substitutions can be made to the technical solutions of the present invention without departing from the essence and scope of the technical solutions of the present invention.
Claims
1. A method for preparing an atomically dispersed iron-based nitrogen-oxygen doped carbon material, characterized in that: The following steps are involved: (1) Mixing solution A and solution B, centrifuging, washing, and evaporating to obtain a precursor; The components of the solution A include dimethylimidazole and iron phthalocyanine; the components of the solution B include zinc nitrate hexahydrate; In the solution A, the concentration of dimethylimidazole is 0.06-0.08 g / mL; in the solution B, the concentration of zinc nitrate hexahydrate is 0.02-0.04 g / mL; the volume ratio of the solution A to the solution B is 1:(0.9-1.1); (2) Carbonizing the precursor, cooling it, washing it, and drying it to obtain the atomically dispersed iron-based nitrogen-oxygen doped carbon material.
2. The method for preparing the atomically dispersed iron-based nitrogen-oxygen doped carbon material according to claim 1, characterized in that: In the step (1), the mass ratio of iron phthalocyanine to dimethylimidazole in solution A is (0.5-1.5):
100.
3. The method for preparing the atomically dispersed iron-based nitrogen-oxygen doped carbon material according to claim 1, characterized in that: In the step (2), the carbonization temperature is 800-1000°C.
4. The method for preparing the atomically dispersed iron-based nitrogen-oxygen doped carbon material according to claim 3, characterized in that: In the step (2), the carbonization conditions are: in an inert atmosphere, heating to 800-1000° C. at a rate of 3-8° C. / min, and then keeping the temperature for 2-5 hours.
5. The method for preparing the atomically dispersed iron-based nitrogen-oxygen doped carbon material according to claim 1, characterized in that: In the step (2), the cleaning includes pickling and water washing; the concentration of the pickling solution used in the pickling is 0.25-0.75M, and the pickling time is 12-72h.
6. The method for preparing the atomically dispersed iron-based nitrogen-oxygen doped carbon material according to claim 5, characterized in that: In the step (2), the washing time is 20-25 hours, and the drying temperature is 60-80°C.
7. The atomically dispersed iron-based nitrogen-oxygen doped carbon material prepared according to the method for preparing the atomically dispersed iron-based nitrogen-oxygen doped carbon material according to any one of claims 1 to 6.
8. The atomically dispersed iron-based nitrogen-oxygen doped carbon material according to claim 7, characterized in that: In terms of mass percentage, the content of iron in the material is 0.2-0.5%.
9. Use of the atomically dispersed iron-based nitrogen-oxygen doped carbon material according to any one of claims 7-8 in wastewater treatment.
10. The use of the atomically dispersed iron-based nitrogen-oxygen doped carbon material in wastewater treatment according to claim 9, characterized in that: The wastewater treatment comprises the following steps: adding the atomic-level dispersed iron-based nitrogen-oxygen doped carbon material and peroxymonosulfate into the wastewater to be treated for treatment.
Citation Information
Patent Citations
Monatomic iron-nitrogen co-doped carbon electrocatalyst as well as preparation method and application thereof
CN111477889A
Preparation and application of iron-nitrogen co-doped porous carbon material
CN114053998A
Atomically dispersed platinum-group metal-free catalysts and method for synthesis of the same
WO2022109337A1
Cited By
Defect-rich iron-nitrogen co-doped porous carbon, preparation method thereof and application of defect-rich iron-nitrogen co-doped porous carbon in degradation of harmful pollutants
CN121426087A